Language of the children adopted to Italy in the adoptive parents’ perspective - Ramonaitė, Jogilė Teresa Teresa (Kalbotyra, 2011)
The article presents the results of a sociolinguistic survey for Italian adoptive parents who have adopted Lithuanian children. The survey is part of an ongoing longitudinal psycholinguistic research on language development in internationally adopted children and it has been conducted in order to gather information about the speed, the level of language acquisition of the adopted children, the attitudes of the adoptive parents towards foreign languages, the assistance for the children learning Italian. The survey results reveal that the majority of the adopted children start to communicate in the new language in a couple of months after arriving in Italy and they reach a perfect or a very good level of Italian. About half of the surveyed children have received assistance when learning Italian from parents or teachers. A vast majority of the adoptive parents consider knowing foreign languages very important and would like their children not to forget Lithuanian (if acquired). Nevertheless, despite the efforts of the adoptive parents or the presence of siblings adopted together, nearly all children maintain no knowledge of Lithuanian after a year in Italy. The most important reasons for that are the desire to adapt to the new environment and the family. In a few cases adoptive parents have understood a clear refusal of the children of anything that had to do with their past, including the language.
Keywords: international adoption; language development; internationally adopted children; language acquisition